Mathematics Education in Different Cultural Traditions- A Comparative Study of East Asia and the West The 13th ICMI Study - Leung, Frederick Koon-Shing; Graf, Klaus-D; Lopez-Real, Francis J. (New ICMI Study Series,, 2006)
In recent years there has been an upsurge of interest concerning international comparisons of mathematics education, stimulated in part by large-scale studies such as TIMSS and PISA. However, many educators have felt that the analysis of such comparisons requires a deep understanding of the underlying cultural and social factors involved, and this perspective led to the 13th ICMI Study Conference being convened to consider the issues. Because of the impossible complexity of trying to cover all different cultural traditions worldwide it was decided to focus on two significant traditions, broadly speaking East Asia and the West. This important volume is the outcome of the ICMI Study. The volume covers a very wide field including the contexts of mathematics education, the curriculum, teaching and learning, and teachers' values and beliefs. Within these broad parameters some of the particular cross-cultural issues that are discussed include intuition and logical reasoning, influences of Confucianism and Ancient Greek traditions, basic skills and process abilities, learners' perspectives, assessment practices, text books and ICT multimedia. Throughout the book emphasis is placed on uncovering and understanding differences and similarities, not just between these two major traditions but within the cultures themselves. Simplistic analyses or solutions are avoided and the authors demonstrate a cultural sensitivity that results in a collaborative, rather than competitive, spirit evident in the comparisons that are made. Much of the focus is on learning together, as much from our failures as our successes. The contributing authors are highly experienced and eminent members of the mathematics education community and together they have provided us with a book that is an invaluable source of information, discussion, reflection and insight. Mathematics Education in Different Cultural Traditions will be of special interest to mathematics teachers, teacher educators, researchers, education administrators, curriculum developers, and student teachers.